Mathematics-I:calculus and linear algebra,for all branches of engineering & technology courses,except cse - Bhui,Bikas Chandra (Vikas Publishing House Pvt. Ltd, 2019)
Mathematics-I:calculus and linear algebra,for all branches of engineering & technology courses,except cse / Bhui,Bikas Chandra. -- Kolkata: Vikas Publishing House Pvt. Ltd., 2019 510 B575 V1 No. of Copies : 1